The association between severity of liver steatosis, apnoea and atherosclerosis risk in OSA patients with NAFLD / Samshol Sukahri - Sukahri, Samshol (2018)
Introduction: Obstructive sleep apnoea (OSA) has been closely associated with nonalcoholic fatty liver disease (NAFLD). It also increases cardiovascular risk and metabolic syndrome. Carotid intima-media thickness (CIMT) is widely used as a reliable index of subclinical atherosclerosis. Thus, this study aimed to determine the relationships between severity of OSA and degree of steatosis and cardiovascular risk via CIMT measurements in a group of OSA patients. Methods: This was a cross-sectional study, conducted at the Faculty of Medicine Uitm. We screened 110 subjects between 18 to 65 years of age, who were diagnosed OSA following sleep study examinations. We excluded patients with seropositive Hepatitis B or Hepatitis C, and significant alcohol intake. Result: The prevalence of NAFLD was 81.8% (n= 90). Almost half of them had NAFLD Stage 1 42.7% (n= 47), 32% (n= 42) had Stage 2 and 1 had Stage 3 (0.9%).The subjects with NAFLD had significantly higher weight compared to those without NAFLD (94.77 kg ± 21.85 vs 74.67 kg ± 16.80, p < 0.001). There were statistically significantly higher mean systolic blood pressure, waist circumference, hip circumference, waist hip ratio and severity of OSA (AHI) among the NAFLD and vs the non NAFLD groups. The mean ICAM-1, Lp(a) and CIMT were significantly higher in the NAFLD group compared to the non-NAFLD group (334.53 ng/mL ± 72.86 vs 265.46 ng/mL ± 102.92, p = 0.001, 85.41 nmol/L ± 52.56 vs 23.55 nmol/L ± 23.66, p <0.001, 0.08 cm ± 0.03 vs 0.06 cm ± 0.01, p = 0.001) respectively. Comparisons between the non-NAFLD, NAFLD 1 and NAFLD 2 groups showed significant differences in systolic blood pressure, diastolic blood pressure, BMI, waist circumference, ICAM-1 and Lp(a) indicating higher cardiovascular risks in the latter 2 groups. Similarly, patients with severe AHI had significantly higher systolic blood pressure, diastolic blood pressure, and waist circumference compared to those with mild AHI and moderate AHI. However, there were no statistically significant differences in mean CIMT values between these 3 groups (mild AHI, moderate AHI and severe AHI, respectively: 0.07 cm ± 0.02 vs 0.08 cm ± 0.03 vs 0.08 cm ± 0.02, p = 0.250). The correlation between stages of NAFLD and the severity of OSA (AHI) was significant by using the Chi-square with p < 0.001 and r = 0.453. Conclusion: This study suggested that the prevalence of NAFLD is alarmingly high in the OSA population. The degree of steatosis in patients with NAFLD was significantly correlated with severity of OSA, CIMT measurements, ICAM-1 and Lp(a). ICAM-1 and Lp(a) are the strong predictors for NAFLD in OSA patients. These findings underscore the significant atherosclerotic risks of these patients and further emphasises the need for a comprehensive cardiovascular risk assessment in this group of high risk patients.